A Critical Analysis of Transboundary Waters of South Asia - Amal Sarkar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
Freshwater is a scarce resource and at a time of its low per capita availability along with high growth rate of population creates a greater necessity to effectively manage this resource. There are 263 transboundary lakes and rivers which take care of nearly 40 % of the world population which lives in these basins. Hence transboundary waters form a significant part of fresh water. Major transboundary waters of South Asia are rivers like Ganga, Indus, Brahmaputra, Kosi, Mahakali, Kabul, Sutlej, Shyok etc. and lakes like Pangong. In India 54% of the area faces at least some level of water stress while in other South Asian nations are facing high water scarcity. Water management and cooperation of transboundary waters in South Asia are highly nationalistic, technocratic and zealously securitized. The author presents a spatial and temporal dimension of disputes of transboundary water bodies between the various South Asian nations. The research article presents the status of water treaties in South Asia and finds that they are not comprehensive as the treaties include only selected transboundary rivers. The author uses mostly secondary data. There is a need for more comprehensive treaties which can provide opportunities for cooperation in irrigation, power generation, flood control and development. Finally, the research article suggests a host of measures like comprehensive water treaties and suggests the future use of these transboundary water bodies change and efforts should be made for changing this zone of conflict to zone of cooperation.